Increased Frequency of Myeloid-Derived Suppressor Cells in Myasthenia Gravis After Immunotherapy - Wang, Yan; Yan, Chong; Su, Caixia; Wang, Ying; Luo, Sushan; Lu, Jun; Zhao, Chongbo; Zhao, Gan; Xi, Jianying (Frontiers in Neurology, 2022)
Myeloid-derived suppressor cells (MDSCs) are a population of myeloid progenitor cells with immunoregulatory functions and their role in myasthenia gravis (MG) was unkonwn. In this study, we investigated the phenotypic and functional alterations of MDSCs in MG before and after immunotherapy. The frequency of MDSCs significantly increased and negatively correlated to that of Th1 or Th17 cells after immunotherapy. MDSCs from therapy naive MG patients showed an impaired suppression on IFN-γ production in T cells and improved immunosuppressive function was identified after immunotherapy. The MFI of Arg-1 in MDSCs also increased after immunotherapy. These findings suggested the functional difference in MDSCs before and after immunotherapy, and MDSCs might play a role in disease remission.